Diagnosis of spiral bevel gear damage using the Wavelet transform model - Tuan Kiet, Vo; Anh Tu, Huynh; Ngoc Duong, Nguyen; Hoa Cuc, Nguyen Thi; Bich Ngoc, Mach Thi; Viet Hung, Pham; Hong Nhung, Cao Thi; Quang Thanh, Nguyen (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2024)
This study applies Wavelet analysis to develop a comprehensive method for detecting damage in spiral bevel gears within automotive drive systems. By utilising Wavelet analysis to examine the vibration signals of the gears, it is possible to identify spatial and temporal variations in the signals, thereby detecting signs of damage in the system. The integration of the Wavelet transform model allows for precise and comprehensive diagnosis of damage issues as well as predicting the vibrations of mechanical systems, particularly in complex meshing models. This not only enhances efficiency and accuracy in the study and handling of gear-related problems but also makes significant contributions to the field of mechanical engineering, especially in gear maintenance and damage diagnosis. Consequently, it improves the reliability and lifespan of automotive drive systems.